Impact of acute exposure to high altitude on anterior chamber geometry - Willmann, Gabriel; Schatz, Andreas; Zhour, Ahmad; Schommer, Kai; Zrenner, Eberhart; Bartz-Schmidt, Karl U.; Gekeler, Florian; Fischer, M. Dominik (Investigative ophthalmology & visual science, 2013)
This study aimed to quantify the impact of exposure to high altitude on individual layers of the cornea in regard to central corneal thickness (CCT) and the geometry of the anterior chamber angle (ACA). This work is related to the Tübingen High Altitude Ophthalmology study. Anterior segment spectral domain optical coherence tomography was used to quantify changes in individual corneal layers and to study ACA and angle opening distance (AOD). Peripheral oxygen saturation, heart rate, and scores of acute mountain sickness (AMS) were assessed in 14 healthy subjects at baseline (341 m) and altitude (4559 m) for respective correlations. Longitudinal analysis revealed a significant (P < 0.05) increase of CCT during altitude exposure (CCTbaseline = 539.27 ± 32.30 μm; CCTday1 = 558.87 ± 29.39 μm; CCTday3 = 567.17 ± 33.40 μm; mean ± SD) due to stromal edema. This change was completely reversible upon descent. Geometric measures of aqueous outflow structures remained consistent with no significant changes in AOD or ACA. Incidence of AMS on day 1 was 64% followed by a decrease in AMS scores over time spent at high altitude; while AMS correlated significantly with stromal edema formation just after arrival (r = 0.71; P = 0.01), no correlation was found on day 3 (r = 0.05; P = 0.87); no correlations were found for vital parameters. Significant stromal edema was found during exposure to high altitude in healthy subjects. This seems to occur due to decreased atmospheric pressure under hypoxia but independent of systemic acclimatization. Other measures of anterior chamber geometry remained stable during the challenge to hypoxic conditions at high altitude.
Gesehen am 15.11.2021